A novel mechanism of rs763110 polymorphism contributing to cervical cancer risk by affecting the binding affinity of C/EBPβ and OCT1 complex to chromatin. Issue 4 (18th November 2016) - Wu, Shenshen; Wang, Shizhi; Fu, You; Tang, Weiyan; Jin, Hua; Meng, Qingtao; Zhang, Chengcheng; Cui, Mengjing; Cao, Xiaoli; Li, Xiaobo; Zhang, Zhengdong; Chen, Rui
Abstract : Recently, several studies have showed that FAS (rs2234767, rs1800682) and FASL (rs763110) functional single nucleotide polymorphisms (SNPs) were associated with the risk of various cancers. However, the association between cervical cancer risk and the three SNPs above remained inconclusive. In this work, we performed a two‐stage case–control study on 1155 cervical cancer patients and 1252 matched healthy controls to determine the roles of the mentioned SNPs in cervical cancer susceptibility. We genotyped the FAS rs2234767, rs1800682, and FASL rs763110 polymorphisms using PCR‐TaqMan assays. Results revealed that the rs763110 TT genotype significantly increased the risk of cervical cancer compared with the CC/CT genotype (adjusted OR = 1.70, 95% CI = 1.19–2.42). However, we did not observe any association between the cervical cancer risk and the rs2234767 and rs1800682 polymorphisms. The immunohistochemistry assay showed that patients carrying the rs763110 TT genotype presented a lower cancerous FASL expression than that of the CC/CT genotypes. Chromatin immunoprecipitation (ChIP) and Sequential Chromatin immunoprecipitation assays also demonstrated that OCT1 was recruited to the FASL promoter region and regulated the FASL gene transcription by interacting with C/EBPβ. In conclusion, this study provided evidence indicating that the rs763110 variant in the FASL promoter was associated with the risk of cervical cancer by affecting the binding affinity of the C/EBPβ/OCT1 complex to chromatin. Abstract : What's new? Genetic variations capable of altering the apoptosis‐initiating function of FAS ‐encoded proteins are known to occur in multiple cancer types. In this study, while investigating the role of FAS single nucleotide polymorphisms in cervical cancer, the authors found that a variant (rs763110) in the ligand gene, FASL, plays a potentially critical role in increasing cervical cancer risk. In particular, the rs763110 TT genotype caused a failure of apoptosis by greatly reducing FASL promoter binding affinity for the transcription factors C/EBPβ and OCT1. Altered FASL transcriptional activity occurred regardless of whether or not cervical cancer cells were infected with human papillomavirus.